Eosinophils capture viruses, a capacity that is defective in asthma. Issue 10 (15th May 2019) - Sabogal Piñeros, Yanaika S.; Bal, Suzanne M.; Dijkhuis, Annemiek; Majoor, Christof J.; Dierdorp, Barbara S.; Dekker, Tamara; Hoefsmit, Esmée P.; Bonta, Peter I.; Picavet, Daisy; van der Wel, Nicole N.; Koenderman, Leo; Sterk, Peter J.; et al.
Abstract: Background: Activated eosinophils cause major pathology in stable and exacerbating asthma; however, they can also display protective properties like an extracellular antiviral activity. Initial murine studies led us to further explore a potential intracellular antiviral activity by eosinophils. Methods: To follow eosinophil‐virus interaction, respiratory syncytial virus (RSV) and influenza virus were labeled with a fluorescent lipophilic dye (DiD). Interactions with eosinophils were visualized by confocal microscopy, electron microscopy, and flow cytometry. Eosinophil activation was assessed by both flow cytometry and ELISA. In a separate study, eosinophils were depleted in asthma patients using anti‐IL‐5 (mepolizumab), followed by a challenge with rhinovirus‐16 (RV16). Results: DiD‐RSV and DiD‐influenza rapidly adhered to human eosinophils and were internalized and inactivated (95% in ≤ 2 hours) as reflected by a reduced replication in epithelial cells. The capacity of eosinophils to capture virus was reduced up to 75% with increasing severity of asthma. Eosinophils were activated by virus in vitro and in vivo. In vivo this correlated with virus‐induced loss of asthma control. Conclusions: This previously unrecognized and in asthma attenuated antiviral property provides a new perspective to eosinophils in asthma. This is indicative of an imbalance between protective and cytotoxic properties by eosinophils that may underlie asthma exacerbations. Abstract : 1, 19 – dioctadecyl ‐ 3, 3, 39, 39 – tetramethylindocarbocyanine (DiD)‐respiratory syncytial virus and DiD‐influenza adhered to human eosinophils. Both viruses were internalized and inactivated by eosinophils. The capacity of eosinophils to capture virus was reduced with increasing severity of asthma. IL‐5 Tg: IL‐5 transgenic; RSV: Respiratory syncytial virus; WT: Wild‐type